Skin Sympathetic Nerve Activity and the Short-Term QT Interval Variability in Patients With Electrical Storm - Chen, Songwen; Meng, Guannan; Doytchinova, Anisiia; Wong, Johnson; Straka, Susan; Lacy, Julie; Li, Xiaochun; Chen, Peng-Sheng; Everett IV, Thomas H. (Frontiers in Physiology, 2021)
Background: Skin sympathetic nerve activity (SKNA) and QT interval variability are known to be associated with ventricular arrhythmias. However, the relationship between the two remains unclear. Objective: To test the hypothesis that SKNA bursts are associated with greater short-term variability of the QT interval (STVQT) in patients with electrical storm (ES) or coronary heart disease without arrhythmias (CHD) than in healthy volunteers (HV). Methods: We simultaneously recorded the electrocardiogram (ECG) and SKNA during sinus rhythm in patients with ES (N=10), CHD (N=8), and during cold-water pressor test in HV (N=12). The QT and QTc intervals were manually marked and calculated within the ECG. The STVQT was calculated and compared to episodes of SKNA burst and non-bursting activity. Results: The SKNA burst threshold for ES and HV was 1.06±1.07μV and 1.88±1.09μV, respectively (P=0.011). During SKNA baseline and burst, the QT/QTc intervals, and STVQT for ES and CHD was significantly higher than that of the HV. In all subjects, SKNA bursts were associated with an increased STVQT (from 6.43±2.99ms to 9.40±5.12ms, P=0.002 for ES; from 9.48±4.40ms to 12.8±5.26ms, P=0.016 for CHD; and from 3.81±0.73ms to 4.49±1.24ms, P=0.016 for HV). The magnitude of increased STVQT in ES (3.33±3.06ms) and CHD (3.34±2.34ms) was both higher than that of the HV (0.68±0.84ms, P=0.047 and P=0.020). Conclusion: Comparted to non-bursting activity, SKNA bursts were associated with a larger increase in the QTc interval and STVQT in patients with heart disease than in HV.